A 224Ra-labeled polyoxopalladate as a putative radiopharmaceutical. Issue 53 (14th June 2019) - Gott, Matthew; Yang, Peng; Kortz, Ulrich; Stephan, Holger; Pietzsch, Hans-Jürgen; Mamat, Constantin
Abstract : A facile preparation of polyoxopalladates with enhanced properties containing radium-224 in the core and a protein corona for further functionalization with targeting (bio)molecules for therapeutic applications in oncology is described. Abstract : Despite their attractive properties, internal targeted alpha therapies using 223/224 Ra are limited to bone-seeking applications. As there is no suitable chelator available, the search for new carriers to stably bind Ra 2+ and to connect it to biological target molecules is necessary. Polyoxopalladates represent a class of compounds where Ra 2+ can be easily introduced into the Pd-POM core during a facile one-pot preparation. Due to the formation of a protein corona, the connection to other targeting (bio)macromolecules is possible.